How much? How fast? How soon? Three simple concepts for progressing training loads to minimize injury risk and enhance performance - Gabbett, T. J. (Journal of Orthopaedic & Sports Physical Therapy, 2020)
Background: When progressing an athlete from rehabilitation to peak performance, load must exceed load-capacity. When gradual, systematic increases in load are applied, load-capacity will improve. However, if the applied load greatly exceeds load capacity, then tissue tolerance is exceeded, and injury may occur. Clinical Question: It is well established that a balance exists between providing an adequate training stimulus to elicit performance benefits while also minimizing the risk of injury. How can practitioners determine how much training is too much? Following injury, how soon can training loads be progressed? How quickly can athletes return to competition? Key Results: When developing rehabilitation or performance programs, three key concepts are critical: the "floor", the "ceiling" and time. The floor represents the athlete`s current capacity, whereas the ceiling represents the capacity needed to perform the specific activities of the sport. A challenge in most sporting environments is the time required to progress from the floor to the ceiling. If athletes` training loads are progressed too rapidly, they will be at increased risk of injury and underperformance. Clinical Application: Rehabilitation practitioners should consider and plan the appropriate amount of time required to progress from the floor (e.g. rehabilitation) to the ceiling (e.g. return to performance). The resilience and robustness that comes from training takes time, and different physical capacities will adapt at different rates. Progressive, gradual, and systematic increases in training load allows athletes to safely progress to the ceiling, reducing injury risk, improving availability, and enhancing performance.